Jenis-jenis Rayap (Isoptera) di Kawasan Hutan Bukit Tengah Pulau dan Areal Perkebunan Kelapa Sawit, Solok Selatan - Alan Handru; Henny Herwina; - Dahelmi (Jurnal Biologi Universitas Andalas, 2012)
An inventarisation of termites (Isoptera) at a fragmented forest (Bukit Tengah Pulau) and palm oil plantation at Solok Selatan was conducted from March to December 2011. Direct sampling method was used to collect termites at three habitats types: forest edge, forest interior, and palm oil plantation. Five species of termites that belonged to two subfamilies were recorded i.e. Hospitalitermes hospitalis Haviland, Longipeditermes mandibulatus Thapa, Nasutitermes sp. (Nasutitermitinae), Termes rostratus Haviland, and Pericapritermes sp. (Termitinae). Four species were found at forest edge, three species at forest interior and two species at palm oil plantation. The only one species (Pericapritermes sp.) was found at all three habitat types.Keywords: termites, forest of Bukit Tengah Pulau, palm plantation, nasutitermitinae, termitinae.